2022
DOI: 10.1007/s11033-022-08162-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the SLCO1B1 A388G single nucleotide polymorphism on the development, clinical parameters, treatment, and survival of multiple myeloma cases in a Polish population

Abstract: Background Multiple myeloma is one of the most common hematological malignancies worldwide. Genetic alterations may lead to the progression from monoclonal gammopathy to multiple myeloma. Additionally, the genetic background of the disease might influence therapy outcomes, including survival time. SLCO1B1, belonging to the OATPs family, is a membrane protein that mediates the uptake of a wide range of endogenous and exogenous (including drugs) compounds. Methods and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A research study in Poland revealed that MM patients possessing the GG genotype of the SLCO1B1 gene’s A388G SNP showed prolonged survival when treated with melphalan-prednisone, compared to other therapies. However, this genetic variant does not elevate the risk of developing MM ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A research study in Poland revealed that MM patients possessing the GG genotype of the SLCO1B1 gene’s A388G SNP showed prolonged survival when treated with melphalan-prednisone, compared to other therapies. However, this genetic variant does not elevate the risk of developing MM ( 35 ).…”
Section: Discussionmentioning
confidence: 99%